2011
DOI: 10.1136/oem.2010.059790
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence within a cohort occupationally exposed to asbestos: a study of dose–response relationships

Abstract: While confirming the established relationship between asbestos exposure and pleuropulmonary and peritoneal cancers, this study also suggests a causal relationship between asbestos exposure and colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Later on, a systematic review showed that none of the various methods used to estimate asbestos exposure yielded consistent exposure–response trends and the strength of the associations was consistently weak or non-existent for four forms of gastrointestinal cancers 3. However, recent studies conducted in a French cohort suggested a positive relationship with colorectal, small intestine and oesophageal cancer 4 5. An earlier literature review also showed that a high level of asbestos exposure, as indicated by a standardised mortality ratio (SMR) for lung cancer of at least 2.0, was associated with elevated SMR for gastrointestinal cancer 6.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, a systematic review showed that none of the various methods used to estimate asbestos exposure yielded consistent exposure–response trends and the strength of the associations was consistently weak or non-existent for four forms of gastrointestinal cancers 3. However, recent studies conducted in a French cohort suggested a positive relationship with colorectal, small intestine and oesophageal cancer 4 5. An earlier literature review also showed that a high level of asbestos exposure, as indicated by a standardised mortality ratio (SMR) for lung cancer of at least 2.0, was associated with elevated SMR for gastrointestinal cancer 6.…”
Section: Introductionmentioning
confidence: 99%
“…The most established occupational risk factor for colon cancer is physical inactivity, 39 which certainly does not characterize chimney sweeping. Some studies suggest an association with asbestos exposure, 40 whereas the effect of diet, alcohol, and tobacco is weak and under debate. 41 Occupational asbestos exposure seems to be the most likely explanation if this cancer is work related, although the chimney sweeps' exposure to asbestos was only moderate.…”
Section: Colon Cancermentioning
confidence: 99%
“…Despite these differences in environmental exposure, asbestos-related stomach cancer following occupational exposure is the best validated to date [10,33–35,5255]. Recently, asbestos exposure is linked with colorectal cancer in 285 cases of cancers while confirming the established relationship between asbestos exposure and pleuropulmonary and peritoneal cancers [56]. Some studies have concluded that a positive association may exist between asbestos exposure and GI cancer [41,44,5661].…”
Section: Epidemiological Evidence: Gastrointestinal Cancers With Asbementioning
confidence: 97%